LEXICAL AND PRAGMATIC ASPECT OF THE TEXT COUPON AS AN ELEMENT OF MULTILEVEL MARKETING - Svetlana Nikolaevna Dubrovina (Вестник Северо-Кавказского федерального университета, 2022)
Coupon as an element of multilevel marketing is analyzed in the system of discourse interaction.